The Concept of Al-Bayān (Clarification) in Islamic Jurisprudence: A Comprehensive Study of its Types, Applications, and Legal Implications: "البيان" في أصول الفقه الإسلامي : دراسة شاملة لأنواعه وتطبيقاته وآثاره الشرعية - Mahmood, Dr. Sajid (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
The discussion on Bayan (Statement/Clarification) constitutes a fundamental pillar of the Usul al-Fiqh (Principles of Jurisprudence), as the derivation of Sharia rulings and the understanding of the Legislator's intent are impossible without grasping its rules and methods. This research aims to meticulously study the concept, divisions, and rulings of Bayan, highlighting its essential function as the unveiling mechanism for meanings potentially obscured within the texts of the Quran and Sunnah. The paper begins by defining Bayan linguistically and technically, followed by an explanation of its general types: Bayan bi al-Fi'l (Statement by Action) (such as the Prophet's performance of prayer and Hajj) and Bayan bi al-Qawl (Statement by Speech). The core of the article delves into the five specific sections of Bayan bi al-Qawl recognized by the Usuliyyun (Jurists): Taqrir (Confirmation), Tafsir (Clarification), Taghyir (Change), Darurah (Necessity), and Tabdil (Substitution/Abrogation). The article illustrates the function of each section using scriptural examples; while Taqrir and Tafsir solidify or reveal the meaning, Taghyir modifies the literal meaning through exceptions or conditions (and must be connected), whereas Tabdil (Naskh) entirely removes the previous ruling and replaces it with a new one (and must be separate). It also sheds light on Bayan al-Darurah, which occurs through silence or circumstantial evidence to alleviate hardship and prevent deception. In conclusion, the research affirms that mastering these divisions represents a comprehensive methodology ensuring the stability of fatwas and the validity of inference, serving as a critical key for the jurist to achieve the precise legal intent in all circumstances.